2019
DOI: 10.1101/738377
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

dsRNA-Seq: Identification of viral infection by purifying and sequencing dsRNA

Abstract: RNA viruses are a major source of emerging and re-emerging infectious diseases around the world. We developed a method to identify RNA viruses that is based on the fact that all RNA viruses produce dsRNA while replicating. Purifying and sequencing dsRNA from total RNA isolated from infected tissue allowed us to recover replicating viral sequences. We refer to this approach as dsRNA-Seq. By assembling dsRNA sequences into contigs we identified full length RNA viruses of varying genome types infecting mammalian … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Previous studies reported that the degree of concentrations for viral RNA sequences in dsRNA-seq data differed from that in virus species ( Urayama et al , 2016 ; Decker et al , 2019 ). We cannot rule out the possibility that some RNA viruses are easier to detect in total RNA-seq than in dsRNA-seq.…”
Section: Resultsmentioning
confidence: 91%
“…Previous studies reported that the degree of concentrations for viral RNA sequences in dsRNA-seq data differed from that in virus species ( Urayama et al , 2016 ; Decker et al , 2019 ). We cannot rule out the possibility that some RNA viruses are easier to detect in total RNA-seq than in dsRNA-seq.…”
Section: Resultsmentioning
confidence: 91%
“…Thus, quantifying pervasive transcription across genes or TEs is sometimes precisely what is being sought, and can be achieved by calculating the ratio between sense and antisense RNA at the features of interest in directional RNA-seq data 111 . More specific approaches have been developed such as dsRNA-seq 184 , which enriches dsRNA by digestion of single-stranded RNA and immunoprecipitation of dsRNA with a sequence-independent anti-dsRNA antibody, followed by sequencing. This approach was originally developed to identify viral dsRNAs.…”
Section: Te-chimeric Transcriptsmentioning
confidence: 99%
“…Given that the sequencing method used to detect the reovirus sequences was designed to enrich for dsRNA and that this virus was undetectable by qRT-PCR it is difficult to fully grasp the viral load in these chameleons. This does, however highlight the utility of dsRNA-seq for the identification of viruses with dsRNA genomes [ 20 ]. The standard shotgun sequencing method we initially used that did not specifically enrich for dsRNA failed to detect the reovirus infection ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…The RNA-seq libraries were sequenced using a dual-indexed, single-end, 1 × 150 method on an Illumina NextSeq 500 instrument with either a NextSeq 500/550 Mid or High Output Kit v2 (150 cycles). An independent metagenomic sequencing run was also performed on the same RNA samples using a library preparation method with enrichment of double-stranded RNA [ 20 ]. This was run on the same platform using a dual-indexed, paired-end, 2 × 75 sequencing method.…”
Section: Methodsmentioning
confidence: 99%